Photon-involving Purification of Water and Air - Pierre Pichat (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
The broad field of photon-involving purification of water and air has given rise to numerous papers, typically dispersed across many journals. Consequently, from time to time, there is a need for a book providing information concerning the different facets of this field in a handy way. In fact, the present book includes both detailed reviews and suitable examples of most of the diverse aspects of the current research. It thus covers processes using sunlight or ultraviolet lamps, chemical oxidants and/or photosensitive semiconductors. The fundamentals, the mechanisms, the materials, and the modeling aspects are all considered throughout the book various sections. The contributions have been written by well-known authors forming an group that guarantees the quality and interest of the book.